SISTEM RELASI JARINGAN SOSIAL DALAM AKTIVITAS PERTAMBANGAN EMAS TANPA IZIN (PETI) DI DESA TANAH BEKALI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Putri, Sahera; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study entiled “Social Networking System Relationships In Gold Illegal Mining Aktivities in the Tanah Bekali Village Pangean Subdistrict Regency Kuantan Singingi”. Researchers are interested in this theme because of the problems that exist in the community about how the people feel about their activity Gold mining Without Permission (PETI). Data analysis was conducted to address the existing problems in this study were analyzed descriptively and qualitatively to illustrate in detail bades on the facts found in the field, regarding relations system social network activity Gold Illegal Mining Without Permission (PETI). Next formulation of the problem: (1) How does the system of relations between elements of society in the activities of Gold Illegal Mining Without Permission (PETI). (2) What is the connection system Gold Illegal Mining Without Permission (PETI) with a group of pro. (3) What is the connection system Golg Illegal Mining Without Permission (PETI) with a group of cons.From the results of research in the field, with their Gold Illegal Mining activities without a permit in the village the ground was very help Tanah Bekali economy and society can also have negative impacts for society and the elvironmen,then the government must eradicate open mining activity and jobs for community.Keywords: Networking System, Relation, Illegal mining